PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN, PERTUMBUHAN PERUSAHAAN DAN EFEKTIVITAS USAHA TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR - Silaban, Dame Prawira; Purnawati, Ni Ketut (E-Jurnal Manajemen; Vol 5 No 2 (2016), 2016)
The purpose of this study was to determine the effect Profitability, Ownership Structure, Corporate Growth and Business Effectiveness against Dividend Policy. Dividend policy is important for investors, because investors tend mengingankan profit to be distributed as dividends, while the company wants on hold in order to finance investment in the future akandating, it is necessary to determine the factors that influence the dividend policy. This study was performed on companies listed in Indonesia Stock Exchange 2010-2013. The number of samples taken is 8 companies. The sampling method in this study using purposive sampling and using regression analysis techniques berganda. This study indicate that profitability, ownership structure, and the effectiveness of efforts partially positive effect on the dividend policy, while the business growth negative effect on dividend policy
Keywords: profitability, ownership structure, rate of growth, effectiveness of the effort, dividend policy.